Prevalence and associated factors of childhood overweight/obesity among primary school children in urban Nepal - Ashmita Karki; Archana Shrestha; Narayan Subedi (BMC, 2019)
Abstract Background Childhood overweight/obesity has become a major public health concern globally because of its adverse health consequences and escalating prevalence. The factors underlying the disease conditions manifested during adulthood commonly originate in childhood. Nepal is going through a transition where under-nutrition co-exists with obesity; however, there is a lack of well-documented information on childhood overweight or obesity in Nepal. This study was carried out to determine the prevalence and associated factors of childhood overweight/obesity among urban primary school children. Methods A cross-sectional survey was conducted from May to October of 2017. Behavioral data were collected using a structured self-administered questionnaire with parents of children aged 6-13 years old in grades 1-5 studying in private schools of Lalitpur district in Nepal. Study participants were selected using two-stage cluster random sampling from 10 private schools. Height and weight measurements of 575 children were taken and BMI-for-age-sex was calculated using WHO AnthroPlus. Data were analyzed using SPSS version 21. Associated factors were examined using Chi-square tests followed by multivariate logistic regression analyses. Results The study found that out of 575 students, 107 (18.6%) were overweight and 41 (7.1%) were obese. Among 328 male children, 62 (19.0%) were overweight and 35 (10.6%) were obese. Likewise, among 247 female children, 45 (18.2%) were overweight and 6 (2.4%) were obese. Male children (aOR = 2.21, 95% CI: 1.38-3.53), children of mothers with a high school (aOR = 3.13, 95% CI: 1.39-7.12) or university level of education (aOR = 3.09, 95% CI: 1.23-7.70) and children of mothers in a professional field (aOR = 1.34, 95% CI: 1.02-4.05) had a greater likelihood of being overweight/obese. Likewise, students consuming energy-dense less nutrient food (aOR = 2.92, 95% CI: 1.66-5.12), lacking active travel to and from school (aOR = 2.38, 95% CI: 1.12-4.79) and those having sedentary behaviors (aOR = 3.01, 95% CI: 1.20-7.29) were likely to be overweight/obese. Conclusions More than one-quarter of the children in urban Lalitpur were found to be overweight/obese. High junk food consumption and sedentary activity were found to be significantly associated with childhood overweight/obesity. School health and awareness programs aiming to reduce the intake of energy-dense foods and promote an active lifestyle including active transportation to school among children are imperative. Future studies to objectively measure the type and amount of food intake and physical activity of students are recommended.